Preliminary investigation of the combined effect of heat treatment and incubation temperature on the viability of the probiotic micro-organisms in freshly made yogurt - Mortazavian, Amir (2006)
The combined effects of heat treatment and incubation temperature were studied on the viability and fermentation time of probiotics in ABY 1 probiotic yogurt (Lactobacillus acidophilus, Bifidobacterium spp. and yogurt bacteria). Three levels of heat treatment (85°C for 30 min, 95°C for 5 min and 95°C for 15 min) and three levels of incubation temperature (37, 40 and 44°C) were selected. At the end of fermentation, the maximum viability of probiotics (for both L. acidophilus and Bifidobacterium spp.) was observed when the milk was heated at 95°C for 15 min and incubated at 37°C. Incubation time was only affected by the incubation temperature and, at 37°C, the longest incubation time of about 6 h was needed to achieve the highest viable counts of L. acidophilus and Bifidobacterium spp.